2006
DOI: 10.1038/nm1394
|View full text |Cite
|
Sign up to set email alerts
|

Engineered heart tissue grafts improve systolic and diastolic function in infarcted rat hearts

Abstract: The concept of regenerating diseased myocardium by implantation of tissue-engineered heart muscle is intriguing, but convincing evidence is lacking that heart tissues can be generated at a size and with contractile properties that would lend considerable support to failing hearts. Here we created large (thickness/diameter, 1-4 mm/15 mm), force-generating engineered heart tissue from neonatal rat heart cells. Engineered heart tissue formed thick cardiac muscle layers when implanted on myocardial infarcts in imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
787
2
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 914 publications
(816 citation statements)
references
References 27 publications
19
787
2
8
Order By: Relevance
“…The constructs appeared to delay the ventricular thinning and led to a reduced increase in the diastolic volume and pressure compared to the sham groups [25]. The constructs were about ~ 400 µm thick and showed vessel formation by the donor cells that supported the construct beyond the 100 µm mark of diffusion limit [26].…”
Section: Engineered Heart Tissues (Ehts)mentioning
confidence: 94%
“…The constructs appeared to delay the ventricular thinning and led to a reduced increase in the diastolic volume and pressure compared to the sham groups [25]. The constructs were about ~ 400 µm thick and showed vessel formation by the donor cells that supported the construct beyond the 100 µm mark of diffusion limit [26].…”
Section: Engineered Heart Tissues (Ehts)mentioning
confidence: 94%
“…This has been shown to improve ECT twitch force production. 26 ECTs formed as hiPSC-CMcontaining fibrin gels were able to displace the microspherecontaining PDMS, which allowed for indirect quantification of the twitch force. While not reported, contraction and relaxation rates can be directly quantified and compared.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these EHTs can be stacked together in various geometries to increase graft size and then stitch the graft to an infarcted heart. Epicardial mapping has shown that paced EHTs propagate electrical signals to the surrounding myocardium, and that these grafts do not lead to arrhythmia [74]. Moreover, echocardiograph and MRI indicated reduced left ventricular dilation and end diastolic volume.…”
Section: Engineered Tissue Constructsmentioning
confidence: 99%
“…1c, d), and then use it to surgically repair the diseased myocardium. Several laboratories are successfully moving toward this goal [48,66,[73][74][75][76]. For example, engineered heart tissue grafts (EHTs) have been developed by seeding neonatal cardiomyocytes in circular molds with collagen and Matrigel, and then culturing the formed rings in a mechanical stretch device [73].…”
Section: Engineered Tissue Constructsmentioning
confidence: 99%
See 1 more Smart Citation